2021
DOI: 10.7717/peerj-cs.658
|View full text |Cite
|
Sign up to set email alerts
|

Digital security vulnerabilities and threats implications for financial institutions deploying digital technology platforms and application: FMEA and FTOPSIS analysis

Abstract: Digital disruptions have led to the integration of applications, platforms, and infrastructure. They assist in business operations, promoting open digital collaborations, and perhaps even the integration of the Internet of Things (IoTs), Big Data Analytics, and Cloud Computing to support data sourcing, data analytics, and storage synchronously on a single platform. Notwithstanding the benefits derived from digital technology integration (including IoTs, Big Data Analytics, and Cloud Computing), digital vulnera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…The digital transformation of the financial sector has significantly increased the complexity and volume of cybersecurity threats, necessitating a comprehensive understanding of the gap between current threats and the solutions available to mitigate them. Edu et al (2021) emphasize the integration of digital technologies such as the Internet of Things (IoT), Big Data Analytics, and Cloud Computing in financial institutions, which, while beneficial, introduces significant vulnerabilities and threats. The study conducted by Edu et al (2021) through a Failure Mode Effect Analysis (FMEA) and the Fuzzy Technique for Order of Preference by Similarity to Ideal Solution (FTOPSIS) highlights the critical vulnerabilities, including insufficient backup electric generators, firewall protection failures, and the absence of information security audits, underscoring the gap in preparedness against digital security threats.…”
Section: Analyzing the Gap Between Current Threats And Solutions In F...mentioning
confidence: 99%
“…The digital transformation of the financial sector has significantly increased the complexity and volume of cybersecurity threats, necessitating a comprehensive understanding of the gap between current threats and the solutions available to mitigate them. Edu et al (2021) emphasize the integration of digital technologies such as the Internet of Things (IoT), Big Data Analytics, and Cloud Computing in financial institutions, which, while beneficial, introduces significant vulnerabilities and threats. The study conducted by Edu et al (2021) through a Failure Mode Effect Analysis (FMEA) and the Fuzzy Technique for Order of Preference by Similarity to Ideal Solution (FTOPSIS) highlights the critical vulnerabilities, including insufficient backup electric generators, firewall protection failures, and the absence of information security audits, underscoring the gap in preparedness against digital security threats.…”
Section: Analyzing the Gap Between Current Threats And Solutions In F...mentioning
confidence: 99%
“…From another approach, the study [51] identified 27 associated factors, of which 5 stand out as the most critical to consider. The first is the lack of a backup electric generator, of which it is indicated that not having at least one creates vulnerability in the digital infrastructure.…”
Section: About the Research Questionsmentioning
confidence: 99%
“…At the same time, the crisis information in network communication has been accelerating to spread and penetrate into the traditional communication field, and its destructive power has been further enhanced. At the same time, due to the weakening of corporate communication control, coupled with the anonymity and concealment of the network, corporate negative information is more likely to be used by competitors, and with the help of online public opinion to artificially expand publicity, even rumors and incitement, making enterprises hard to prevent [5].…”
Section: Network Communication Boosts Enterprise Crisismentioning
confidence: 99%